The Impact of Memorable Tourist Experiences on Satisfaction, Word-of-Mouth, and Revisit Intentions At Bamboo Udjo Ecoland Conservation Tourism - Fadillah Nur Islami; Enok Maryani; Rini Andari (Journal of Indonesian Tourism and Development Studies, 2025)
The global tourism industry is undergoing a significant shift toward sustainable tourism concepts that emphasize not only economic growth and visitor numbers but also environmental and cultural preservation. This study aims to examine the effects of various dimensions of Memorable Tourism Experience (MTE)—including hedonism, involvement, knowledge, local culture, meaningfulness, novelty, and refreshment—on visitor satisfaction. Additionally, it explores how visitor satisfaction impacts Positive Word of Mouth (PWOM) and Revisit Intention at Udjo Ecoland, a bamboo conservation destination in Bandung. Using a quantitative survey of 206 respondents, data were analyzed through Structural Equation Modeling (SEM) with SmartPLS. Results indicate that active involvement (β=0.274; p=0.000), knowledge (β=0.128; p=0.043), local culture (β=0.205; p=0.002), and novelty (β=0.143; p=0.025) significantly affect visitor satisfaction, while hedonism, meaningfulness, and refreshment do not show significant effects. Visitor satisfaction strongly drives PWOM (β=0.427; p=0.000) and revisit intention (β=0.422; p=0.000), with PWOM also reinforcing revisit intention (β=0.422; p=0.000). Mediation analysis confirms visitor satisfaction as a mediator linking MTE to promotional behavior and visitor loyalty. These findings underscore the importance of developing interactive, educational, and culturally rooted tourism experiences to enhance visitor loyalty and sustain conservation destinations. This study contributes theoretically and offers practical recommendations for destination managers to design responsible and value-added sustainable tourism strategies. Keywords: Memorable Tourism Experience; Visitor Satisfaction Word Of Mouth, Revisit Intention, Bamboo Conservation, Sustainable Tourism